Auxological and Endocrinological Features in Children With McCune Albright Syndrome: A Review - Tufano, Maria; Ciofi, Daniele; Amendolea, Antonella; Stagi, Stefano (Frontiers in Endocrinology, 2020)
McCune–Albright syndrome is a rare and complex congenital sporadic disease involving the skin, skeleton and endocrine system with a prevalence ranges from one in 100,000 to 1,000,000. In addition to the classical triad of fibrous dysplasia of bone, café au lait skin pigmentation and precocious puberty, other multiple endocrinopathies, including hyperthyroidism, growth hormone excess, hypercortisolism, and hypophosphatemic rickets, could be associated. A brief review of the syndrome in children is here reported.